The Relationship between an Emerging Grounded Theory and the Existing Literature - Vivian B. Martin (Grounded Theory Review: An International Journal, 2006)
The relationship between grounded theory researchers and the existing literature has become a red herring that even confuses some grounded theorists who have completed a study. Antoinette McCallin’s essay does a commendable job outlining the realities of the research terrain that make proceeding without some exposure to the literature unlikely and ill-advised in most situations. When embarking on my dissertation, I needed to know enough about the literature, both substantive and methodological, to argue for the use of classic grounded theory as opposed to many other choices within my field; yet my study benefited from the necessary tensions between the emerging grounded theory and the existing literature. In this brief essay I propose that the relationship between the existing literature and a developing grounded theory project goes through four discernible phases: noncommittal, comparative, integrative, and, if the analyst can push, a transcendent phase in which the theory is not simply one of a number of theories of a kind within the discipline’s literature. I explain the phases to make more explicit the underrecognized subversive potential of grounded theory to push pass disciplinary boundaries by broadening the ‘relevant’ literature. Barney Glaser has often admonished grounded theory researchers to put off the literature to avoid wasting time and energy with literature that may prove irrelevant. I have not found such literature to be irrelevant as much as limited, and in some  cases restricted by what a particular discipline defines as the appropriate literature. Therefore, the question of what literature offers possibilities for literature review and comparisons that would allow for richer knowledge generation. I return to this matter toward the end of the essay.